Comparative Evaluation of Film Thickness and Net Setting Time of Fuji I with a New Glass Ionomer Cement - fatemeh raoufinejad; baharan ranjbar omidi; siavash kamali; fahimeh nouri; Faranak Solgi (مجله علمی دانشگاه علوم پزشکی کردستان, 2020)
Background and Aim: Glass Ionomer cements have been used widely due to their biocompatibility, fluoride release and the ability to decrease the incidence of marginal caries. Minimum film thickness, adequate net setting time & high compressive strength are the main characteristics of a luting cement in clinical dentistry. The purpose of this study is to compare the film thickness & net setting time of Fuji I and a newly developed GIC. Materials and Methods: 20 samples were prepared with P/L of 1.8:1 for Fuji I & 0.72:0.4 for Iranian cement. For the determination of net setting time, 5×8×10mm metal mold was prepared. Ninety seconds after mixing, carefully lower the indenter 0.1±1mm diameter vertically on the surface of the cement. Repeating the indentations at 30 s. Net Setting Time was recorded as the time elapsed between the end of mixing time and the time when the needle failed to make a complete circular indentation. For the determination of film thickness, two flat glass plates was used and the thickness of both were measured with micrometer device. Then applied a 0.1ml of the mixed cement at the center of the lower plate and applied 150N force to the specimen via the top plate. Then measured the difference of the two plates thickness with and without the cement as the film thickness of the cement. The data were entered into SPSS21 software and Kolmogorov Smirnov and independent T-test were used to evaluate the data. Results: Fuji I had shorter mean value of Net setting time and smaller film thickness than Iranian cement.This difference was statistically significant. Conclusion: Fuji I seems a better clinical choice for the cementation of indirect restorations than Iranian cement.